BUSINESS ETHICS: PENGARUH TERHADAP TRANSAKSI E-COMMERCE DALAM PERSFEKTIF EKONOMI ISLAM - Handayani, Tia Sari; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2022)
The number of E-Commerce sites that have sprung up along with the development of information technology and penetration of the internet network in urban to rural communities, these developments also spread to the Muslim market sector. This study aims to determine the extent to which the influence of Islamic business ethics in online buying and selling is implemented on e-Commerce sites. This research is a descriptive study with an analytical approach and data collection of several literature studies using several journals as well as some of the best and most updated articles. Through the research, it is hoped that the practice of buying and selling online that occurs on e-Commerce sites is actually carried out in accordance with the business ethics of buying and selling in Islam